THE ROLE OF CHILDREN LITERATURE TO EXPOSE STUDENTS TOWARDS LEADERSHIP AND BROTHERHOOD VALUE - Mukaromah, Dyah (Universitas Muhammadiyah Surakarta, 2018)
folktales and short stories will encourage children to love language, grow their interest in culture as well as strengthen their character building. In the other side, teachers often find it difficult to find ways to teach children about all those three matters. This paper will present how children literature play its significant role in exposing children towards character building, especially on leadership and brotherhood value. It will discuss a well known children short story tittled “The Scarlet Ibis” by James Hurst. A story, full packed by the expression of love from an older brother to his younger brother, and his way of leading his younger brother as well. It is proven from the analysis that the story can be designed as teaching material for children so that they are exposed towards leadership and brother value. On the expectation that they will grow to be a wise and thoughtful person with a decent personality and intelegence. Key words: children literature, leadership, brotherhood